Orthogonal Latin hypercube designs for three columns - Parui, Shyamsundar; Mandal B.N.; Parsad, Rajender; Dash, Sukanta (Utilitas Mathematica, 2018)
In this article, we give a complete solution to the construction problem of second order orthogonal Latin hypercube designs for any number of rows for three columns by combining smaller orthogonal designs except for the number of rows n = 4 (mod 8). However, we have given solution for first order orthogonal Latin hypercube designs for the number of rows n = 4 (mod 8) for three columns. © 2018 Utilitas Mathematica Publishing Inc. All rights reserved.